2013
DOI: 10.1111/jnc.12107
|View full text |Cite
|
Sign up to set email alerts
|

15‐Deoxy‐Δ12,14‐prostaglandin J2 (15d‐PGJ2) protects neurons from oxidative death via an Nrf2 astrocyte‐specific mechanism independent of PPARγ

Abstract: Astrocytes are critical for the antioxidant support of neurons. Recently, we demonstrated that low level hydrogen peroxide (H 2 O 2 ) facilitates astrocyte-dependent neuroprotection independent of the antioxidant transcription factor Nrf2, leaving the identity of the endogenous astrocytic Nrf2 activator to question. In this study, we show that an endogenous electrophile, 15-deoxy-D12,14-prostaglandin J2 (15d-PGJ2), non-cell autonomously protects neurons from death induced by depletion of the major antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Another example is the anti-inflammatory prostaglandin 15d-PGJ 2 , which positively regulates the NRF2 pathway producing a conformational change in KEAP1 protein that allows the translocation of NRF2 to nucleus [38]. Furthermore, NRF2 knockdown in astrocytes abrogated the neuroprotective effect of 15d-PGJ 2 , as well as 15d-PGJ 2 -facilitated ARE-dependent antioxidant enzyme gene induction [9]. Both pathways are regulated by paliperidone in animal models of acute/chronic stress and could be implicated, at least in part, in the effects reported here [25,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is the anti-inflammatory prostaglandin 15d-PGJ 2 , which positively regulates the NRF2 pathway producing a conformational change in KEAP1 protein that allows the translocation of NRF2 to nucleus [38]. Furthermore, NRF2 knockdown in astrocytes abrogated the neuroprotective effect of 15d-PGJ 2 , as well as 15d-PGJ 2 -facilitated ARE-dependent antioxidant enzyme gene induction [9]. Both pathways are regulated by paliperidone in animal models of acute/chronic stress and could be implicated, at least in part, in the effects reported here [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ may be also activated by the antidiabetic thiazolidinedione drugs, which exert anti-inflammatory, antiexcitotoxic, and proenergetic effects in the brains of stressed rats [7,8]. The antioxidant profile of 15d-PGJ 2 / PPARγ may be related to its ability to regulate the nuclear factor erythroid-related factor 2 (NRF2), in brain [9]. Inactive NRF2 is retained in the cytoplasm by association with the kelch-like ECH-associated protein 1 (KEAP1), but during inflammation or oxidative stress, the phosphorylation of some intracellular kinases, such as phosphoinositide 3-kinase (PI3K) and protein kinase B (AKT), elicits the translocation of NRF2 to the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that, due to its special α,β- unsaturated carbonyl groups that act as an electrophilic center, 15d-PGJ2 could bind to the cysteine residue of Keap1, separate the Keap1-Nrf2 complex, and thus liberate Nrf2 from Keap1-dependent repression so that Nrf2 accumulates in the nucleus [44] . Indeed, our study observed and detected the nuclear expression of Nrf2 ( Figure 5B, 5C).…”
Section: Discussionmentioning
confidence: 99%
“…Similar concentrations of 15d-PGJ 2 enhance reactive oxygen species and induce human neuronal cell death through the modification of Cys35 and Cys69 within thioredoxin, an enzyme important for protection against oxidative stress (112). In contrast, lower concentrations of cyPG administration afford astrocyte-dependent neuroprotection in a GSH depletion model of cell death (113). Thus, excessive α,β-unsaturated ketone concentrations impart proinflammatory effects, impacting disease pathophysiology (114, 115) and emphasizing the need for strict control of the levels of these mediators in vivo.…”
Section: Pleiotropic Signaling Actions Of Electrophilic Fatty Acidsmentioning
confidence: 99%